We have the function f(x) = cos 2x /(sin x)^2*(cos x)^2

cos 2x = (cos x)^2 - ( sin x)^2

=> cos 2x /(sin x)^2*(cos x)^2

=> [(cos x)^2 - ( sin x)^2] / (sin x)^2*(cos x)^2

=> 1/ (sin x)^2 - 1/ (cos x)^2

=> (cosec x)^2 - (sec...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have the function f(x) = cos 2x /(sin x)^2*(cos x)^2

cos 2x = (cos x)^2 - ( sin x)^2

=> cos 2x /(sin x)^2*(cos x)^2

=> [(cos x)^2 - ( sin x)^2] / (sin x)^2*(cos x)^2

=> 1/ (sin x)^2 - 1/ (cos x)^2

=> (cosec x)^2 - (sec x)^2

So, Int [ f(x)]

=> Int [ (cosec x)^2 - (sec x)^2 dx]

=> Int [(cosec x)^2 dx] - Int [(sec x)^2 dx]

=> - tan x - cot x + C

**Therefore the required antiderivative of f(x)=cos2x/(sin^2x)*(cos^2x) = -tan x - cot x + C**